Muscle metabolic determinants of exercise tolerance following exhaustion: relationship to the “critical power” - Chidnok, Weerapong; Fulford, Jonathan; Bailey, Stephen J.; DiMenna, Fred J.; Skiba, Philip F.; Vanhatalo, Anni; Jones, Andrew M. (Journal of applied physiology (1985), 2013)
We tested the hypothesis that muscle high-energy phosphate compounds and metabolites related to the fatigue process would be recovered after exhaustion during recovery exercise performed below but not above critical power (CP) and that these changes would influence the capacity to continue exercise. Eight male subjects completed single-leg, knee-extension exercise to exhaustion (for ∼180 s) on three occasions, followed by a work-rate reduction to severe-intensity exercise, heavy-intensity exercise (<CP), or a 10-min passive recovery period, in random order. The muscle metabolic responses to exercise were assessed using 31 P magnetic resonance spectroscopy. There was a significant difference between the sustainable exercise duration during the recovery from exhaustive exercise between the <CP and >CP conditions (at least 10 min and 39 ± 31 s, respectively; P < 0.05). During passive recovery and <CP recovery exercise, muscle phosphocreatine concentration ([PCr]) increased rapidly after the exhaustion point, reaching ∼96% and ∼76% of baseline values, respectively, after 10 min ( P < 0.05). Moreover, pH increased abruptly, reaching 7.0 ± 0.0 and 7.0 ± 0.2, respectively, after 10 min recovery ( P < 0.05). However, during >CP recovery exercise, neither muscle [PCr] nor pH recovered, reaching ∼37% of the initial baseline and 6.6 ± 0.2, respectively. These results indicate that the muscle metabolic dynamics in recovery from exhaustive >CP differ according to whether the recovery exercise is performed below or above the CP. These findings confirm the importance of the CP as an intramuscular metabolic threshold that dictates the accumulation of fatigue-related metabolites and the capacity to tolerate high-intensity exercise.